Genistein mitigates diet-induced obesity and metabolic dysfunctions in gonadectomized mice with some sex-differential effects - Kositanurit, Weerapat; Siritaweechai, Natakorn; Varachotisate, Pachara; Burana, Chuti; Sukswai, Narittee; Surintrspanont, Jerasit; Siriviriyakul, Prasong; Kaikaew, Kasiphak; Werawatganon, Duangporn (Frontiers in Endocrinology, 2024)
Background Obesity is associated with insulin resistance (IR) and metabolic dysfunction-associated steatotic liver disease (MASLD). Genistein, an isoflavone, is a promising natural compound for preventing and treating obesity and metabolic dysfunctions. We aimed to investigate the sex-specific protective effects of genistein on obesity, IR, and MASLD in a murine model of sex hormone deprivation with diet-induced obesity (DIO), mimicking postmenopausal women or aging men with metabolic syndrome. Methods Gonadectomized and sham-operated C57BL/6NJcl mice were fed a high-fat high-sucrose diet for 4 weeks to induce obesity (7 mice per group). In gonadectomized mice, genistein (16 mg/kg/day) or vehicle (7.5% dimethyl sulfoxide) was orally administered for 45 days. We assessed glucose homeostasis parameters, hepatic histopathology, and hepatic gene expression to investigate the effects of gonadectomy and genistein treatment. Results Gonadectomy exacerbated adiposity in both sexes. Ovariectomy diminished the protective effects of female gonadal hormones on the homeostatic model assessment for insulin resistance (HOMA-IR), serum alanine transaminase levels, hepatic steatosis score, and the expression of hepatic genes associated with MASLD progression and IR, such as Fasn, Srebf1, Saa1, Cd36, Col1a1, Pck1, and Ppargc1a. Genistein treatment in gonadectomized mice significantly reduced body weight gain and the hepatic steatosis score in both sexes. However, genistein treatment significantly attenuated HOMA-IR and the expression of the hepatic genes only in female mice. Conclusion Genistein treatment mitigates DIO-related MASLD in both male and female gonadectomized mice. Regarding hepatic gene expression associated with MASLD and IR, the beneficial effect of genistein was significantly evident only in female mice. This study suggests a potential alternative application of genistein in individuals with obesity and sex hormone deprivation, yet pending clinical trials.